The influence of adding of modified ZrO2-TiO2 nanoparticles on certain physical and mechanical properties of heat polymerized acrylic resin - Tiba A Salman; Hanan A Khalaf (College of Dentistry/ University of Baghdad, 2015)
Background: The mechanical and physical properties of Polymethyl methacrylate (PMMA) don'tfulfill the entire ideal requirements of denture base materials. The purpose of this study was to produce new modified polymer nanocomposite (PMMA /ZrO2-TiO2) andassess itsimpact strength, transverse strength and thermal conductivity in comparison to the conventionalheat polymerized acrylic resin. Materials and Methods: Both ZrO2 and TiO2nano fillers were silanized with TMSPM (trimethoxysilyl propyl methacrylate) silane coupling agent before beingdispersed by ultrasonication with the methylmethacrylate (monomer) and mixed with the polymer by means of 2% by weight in (1:1) ratio, 60 specimens were constructed by conventional water bath processing technique and divided into 2 groups: 30 specimens for control group 0% nanofillers and 30 specimens for experimental group 2% of (1:1) ZrO2 and TiO2nano fillers then each group was subdivided into3 sub-groups according to the test to be conducted with 10 specimens for impact, transverse and thermal conductivity test. Results: The interaction of TMSPM silane and the nanofillers was confirmed by FT-IR (Fourier Transform Infra-red spectrophotometer). High significant increase in impact strength (9.838) Kj/m2 and transverse strength (101.705) N/mm2 and non-significant increase in thermal conductivity (0.286) W/m.C° of heat cured acrylic resin of the new polymer nanocomposite were observed. Conclusions: The addition of 2 wt.% of ZrO2:TiO2 by means of 1:1 ratio considerably improved the impact and transverse strength and had a positive effect on the thermal conductivity.